The role of meal viscosity and oat [beta]-glucan characteristics in human appetite control: a randomized crossover trial - Rebello, Candida J; Chu, Yi-Fang; Johnson, William D; Martin, Corby K; Han, Hongmei; Bordenave, Nicolas; Shi, Yuhui; O'Shea, Marianne; Greenway, Frank L (Nutrition journal, 2014)
Foods that enhance satiety can help consumers to resist environmental cues to eat, and improve the nutritional quality of their diets. Viscosity generated by oat [beta]-glucan, influences gastrointestinal mechanisms that mediate satiety. Differences in the source, processing treatments, and interactions with other constituents in the food matrix affect the amount, solubility, molecular weight, and structure of the [beta]-glucan in products, which in turn influences the viscosity. This study examined the effect of two types of oatmeal and an oat-based ready-to-eat breakfast cereal (RTEC) on appetite, and assessed differences in meal viscosity and [beta]-glucan characteristics among the cereals. Forty-eight individuals were enrolled in a randomized crossover trial. Subjects consumed isocaloric breakfast meals containing instant oatmeal (IO), old-fashioned oatmeal (SO) or RTEC in random order at least a week apart. Each breakfast meal contained 218 kcal (150 kcal cereal, and 68 kcal milk) Visual analogue scales measuring appetite were completed before breakfast, and over four hours, following the meal. Starch digestion kinetics, meal viscosities, and [beta]-glucan characteristics for each meal were determined. Appetite responses were analyzed by area under the curve. Mixed models were used to analyze response changes over time. IO increased fullness (p = 0.04), suppressed desire to eat (p = 0.01) and reduced prospective intake (p < 0.01) more than the RTEC over four hours, and consistently at the 60 minute time-point. SO reduced prospective intake (p = 0.04) more than the RTEC. Hunger scores were not significantly different except that IO reduced hunger more than the RTEC at the 60 minute time-point. IO and SO had higher [beta]-glucan content, molecular weight, gastric viscosity, and larger hydration spheres than the RTEC, and IO had greater viscosity after oral and initial gastric digestion (initial viscosity) than the RTEC. IO and SO improved appetite control over four hours compared to RTEC. Initial viscosity of oatmeal may be especially important for reducing appetite.